Meningkatkan Kemampuan Motorik Halus Anak Usia 4 – 5 Tahun melalui Kolase dari Bahan Bekas di TK ABA III Kota Probolinggo - Uhriyah, Sulfi; Lorenza, Dina Dwi; Windasari, Indriana Warih (Asian Journal of Early Childhood and Elementary Education, 2023)
By using collages made from used materials, this research seeks to help children at TK ABA III PROBOLINGGO CITY develop their fine motor skills. The research utilized in this study is based on classroom action (PTK). This study was conducted in two parts. with three sessions in each cycle. Twelve children, seven of them girls and five boys, aged four to five years, were the subjects of the study. Documentation and observation techniques were used in data collection. Research findings show that children aged 4 to 5 years benefit from collage activities that reuse materials, as seen by the children's progress from cycle I to cycle II.